Pengembangan Aplikasi Menu Makanan dengan Metode Kanban Berbasis Web pada Kantin 40 Basemen UNPAM - Multiana Multiana; Putri Khoiriah Harahap; Sinta Mutiara (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Advances in information technology have led to digital transformation in various business sectors, including small businesses such as campus canteens. Currently, the Basement 40 Canteen at Pamulang University still uses manual methods for menu selection and order analysis, which causes a number of problems, including poor service, difficulties in the recording process, and a lack of transparency in the workplace. The purpose of this study is to develop a web-based application that uses the Kanban method to improve operational efficiency and create clearer work processes. The methodology used is descriptive qualitative with Agile system development based on the Kanban methodology. Direct observation, interviews with canteen managers, and document analysis were used to collect data. The implementation of Kanban involves the use of visuals to display the work process in three stages: "To Do, Doing, and Done" calculating the amount of work in progress (WIP), and continuously making adjustments. The findings of the study indicate that the application created facilitates menu selection, simplifies order status monitoring, and reduces difficulties in the delivery process. The results of the evaluation regarding the use of the system indicate that this system is easy to use and can improve work effectiveness and efficiency. This research is expected to provide a practical overview of the campus digitalization process and enhance academic understanding of the application of Agile methods in small-scale business information systems.